+0  
 
0
160
2
avatar

Simplify and factor the expression n(n+3)-4. Show that the original expression and the factored form have the same value for n=0,1,2,3,and 4.

 Aug 30, 2018

Best Answer 

 #2
avatar+27547 
+1

n(n + 3) - 4  =  n^2 + 3n - 4 = (n + 4)(n - 1)

 

.

 Aug 31, 2018
 #1
avatar+27 
+1

n(n+3)-4

2n+3n-4 

 

If n is 0 

2*0+3*0 -4

0+0-4

=4 

 

if n is 1 

2*1+3*1+-4

5-4=1

 

If n is 2 

4+6-4

6

 

If n is 3

6+9-4

11

 

If n is 4 

8+12-4

16 

 

wink

 Aug 31, 2018
 #2
avatar+27547 
+1
Best Answer

n(n + 3) - 4  =  n^2 + 3n - 4 = (n + 4)(n - 1)

 

.

Alan Aug 31, 2018

6 Online Users

avatar